User education programme in Nigerian university libraries; a need for restricting (2000)
User education programme in university libraries in Nigeria needs reviewing if libraries are to justify their establishment in the university system. It is at the moment restricted to the orientation aspect alone without the instruction component. This paper attempts to establish why and what impact a user education programme should have on student life even after university education. The paper also suggests ways of improving education programme by making it a three-year programme to be imbibed throughout the student stay in the University. Of crucial importance are programme duration, timing and presentation. For the programme to be effective, planning and periodic evaluation of the programme must be considered.